The Most Important Aspects Of The Democratic Governance Style In The Modern Human Resources Management System - Iroda Bakiyeva; Sarvar Rustamov (Indonesian Journal of Innovation Studies, 2022)
The modern human resources management system requires a manager to feel highly human. Therefore, research is a dose. The article analyzed the comparison of management styles and made conclusions through deductive methods.